Pengaruh Gaya Kepemimpinan ,Kompetensi Manajemen Sumber Daya Manusia dan Transparansi Terhadap Akuntabilitas Pengelolaan Keuangan Dana - Kastanya, Mensy Otelyo; Ipijei, Irene (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Influence of Leadership Style, Human Resource Competency and Transparency on the Accountability of Village Fund Financial Management in Jagebob District. This research aims to determine (1) the influence of leadership style on village fund accountability (2) the influence of human resource competency on accountability (3) the influence of transparency in village funds on accountability (4) the influence of leadership style, human resource competency and transparency on management accountability village funds. This type of research is quantitative, the sample in this research is the entire community which is part of the total population which can provide 60 data. The sampling technique is simple random sampling (simple sample). Data collection was carried out by filling out research questionnaires. For data analysis, descriptive statistical analysis was used with the help of statistical analysis tools, namely SPSS Version 22 IMB. The results of statistical testing, namely reliability tests for all variables, are reliable because Cronbach's alpha (α) value is > 0.70, namely accountability 0.891, leadership style 0.810, competence 0.819, and transparency 0.843. Partial testing was 448,046> Ftable, namely 2.03 with a value of 0.000<0.05. The determination test was 95.8% with the influence of other variables being 4.2%. The partial test of all variables was accepted with a value of count <ttable for each leadership style variable 3.233<0.003, HR competency 2.249<0.000, and transparency 4.354<0.042. The regression test is that the leadership style variable (X1) is 0.142, competence (X2) 0.146, and transparency (X3) 0.260 on accountability (Y) with a significant value smaller than 0.05. The results of the research can be concluded that (1) leadership style has a positive effect and significant impact on village fund accountability (2) human resource competency has a positive and significant impact on accountability (3) transparency has a positive and significant impact on accountability (4) leadership style, human resource competency, and transparency have a positive and significant impact on accountability in managing village funds.